Web-based lifelong learning platform with peer tutoring - Evy Widya (Nanyang Technological University, 2023)
The improvement of digital technologies and the ease of access to the Internet have drastically changed the way people live their everyday lives. The education system around the world has been constantly changing to keep up in this digital age. The changes in the online learning have opened a new learning opportunity which led to the development of Massive Open Online Courses. With the increasing popularity of the online learning, more and more people registered an account in various online learning platforms to upgrade their skills.